Analisis Penyebab Reject Part A Pada Proses Produksi Menggunakan Seven Tools di PT XYZ - Sari, Tika Wulan; Azizah, Fahriza Nurul (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2025)
In the manufacturing industry, product quality is the main benchmark that determines the competitiveness of a company. PT XYZ Industri as one of the main suppliers of national automotive components, faces the problem of high numbers of reject products, especially in the Panel Wheel House part in the E-Line production line. This study aims to analyze the main causes of these reject products and provide suggestions for improvement through the application of the Seven Tools method as a quality control tool. The study was conducted using a case study approach using production data from January to March 2024. Data collection methods include direct observation, interviews with related parties, and documentation studies of daily production reports. There are two dominant types of defects in the Pnl Wheel House part, namely neck and crack, which are identified through the Pareto Chart and Check Sheet. Furthermore, Fishbone Diagram analysis is used to determine the root of the problem involving machine, method, and material factors. The results of the study show that neck defects dominate with a proportion of 98%, which is caused by unstable cushion pressure and die design that is prone to causing imperfect pulling in the drawing process. The application of the Control Chart shows process inconsistencies, which are then corrected by revising the control limits. Improvement strategies are formulated using the 5W+1H method, such as standardization of cushion pressure and routine inspection of die conditions and raw material quality. By implementing this approach, PT XYZ can significantly improve production quality, reduce reject rates, and increase efficiency and customer satisfaction. This study proves that Seven Tools is an effective method in identifying and handling quality problems in the manufacturing process